Insight of PBZ mediated drought amelioration in crop plants - Maheshwari, Chirag; Garg, Nitin Kumar; Hasan, Muzaffar; V, Prathap; Meena, Nand Lal; Singh, Archana; Tyagi, Aruna (Frontiers in Plant Science, 2022)
Water scarcity is a significant environmental limitation to plant productivity as drought-induced crop output losses are likely to outnumber losses from all other factors. In this context, triazole compounds have recently been discovered to act as plant growth regulators and multi-stress protectants such as heat, chilling, drought, waterlogging, heavy metals, etc. Paclobutrazol (PBZ) [(2RS, 3RS)-1-(4-chlorophenyl)- 4, 4-dimethyl-2-(1H-1, 2, 4-trizol-1-yl)-pentan-3-ol)] disrupts the isoprenoid pathway by blocking ent-kaurene synthesis, affecting gibberellic acid (GA) and abscisic acid (ABA) hormone levels. PBZ affects the level of ethylene and cytokinin by interfering with their biosynthesis pathways. Through a variety of physiological responses, PBZ improves plant survival under drought. Some of the documented responses include a decrease in transpiration rate (due to reduced leaf area), higher diffusive resistance, relieving reduction in water potential, greater relative water content, less water use, and increased antioxidant activity. We examined and discussed current findings as well as the prospective application of PBZ in regulating crop growth and ameliorating abiotic stresses in this review. Furthermore, the influence of PBZ on numerous biochemical, physiological, and molecular processes is thoroughly investigated, resulting in increased crop yield.